Final answer:
To solve (9x + 13), we simplify it to 9x + 31. For (12x - 29), it remains unchanged.
Step-by-step explanation:
To solve the expression (9x + 13), we use the distributive property, which states that for any real numbers a, b, and c, a(b + c) = ab + ac. Applying this property, we have:
- 9x + 13 = 9x + 9(2) + 13 = 9x + 18 + 13 = 9x + 31
Thus, the expression (9x + 13) simplifies to 9x + 31.
Similarly, to solve the expression (12x - 29), we use the distributive property:
- 12x - 29 = 12x - 10 - 19 = 12x - 29
Therefore, the expression (12x - 29) remains unchanged.
Learn more about Simplifying expressions using the distributive property